Evaluación de diferentes niveles de extracto de piñón (Jatropha curcas L.) para el control de garrapatas en bovinos - Loor Cedeño, Luis Eduardo (2023)
The present study consisted of evaluating levels of aqueous extract of pinyon leaves (Jatropha curcas L.) (T1): 8%, (T2): 10%, (T3): 12%, (T4): 14 % y (T0): ethion + cypermethrin, for the control of ticks in cattle from the Los Potreros ranch, Boyacá site, Chone, Manabí; for this, a completely randomized design (DCA) was used, the statistical assumptions of normality of errors (Shapiro-Wilk), analysis of variance and post hoc Tukey 5% test were applied. The results determine that on day 1 (T0) it shows the highest mortality rate in ticks at 24 hours with 87%, 48 hours with 95% and 72 hours with 100% all with p<0.0001; on day 15 (T4) it shows the highest mortality rate in ticks at 24 hours with 28%, 48 hours with 63% both with p<0.0001 and 72 hours with 91% p<0.0002; on day 30 (T0) shows the highest mortality rate in ticks at 24 hours with 36% p<0.0001, (T0, T2 and T4) at 48 hours with 36% p<0.0001 and 72 hours (T2 and T4) with 48% and 50% p<0.0001, which allows conjecturing that the extract of pinyon leaves has ixodicidal effects on ticks in a 14% solution; the different levels of the extract did not present allergenic effects in the animals. The T4 is an economical alternative to achieve lower tick mortality by ± 1 percentage point in relation to the control, with a cost of $0.30 less than this.